COVID-19 Breakthrough Infections Among Medical Students Under the SLICE and CLARO Programs: Ateneo School of Medicine and Public Health Experience - Carlos-Dollaga, Princess D.L. (Archīum Ateneo, 2024)
Objective This study aims to report the incidence and characteristics of breakthrough infections among medical students in the first Philippine private medical school that resumed limited face-to-face classes and clinical rotations from July to December 2021. Methods This is a descriptive study using secondary worksheet from multiple-source records review of breakthrough infections among medical students from July to December 2021. Results Among the 837 vaccinated medical students, 23 (2.7%) experienced COVID-19 breakthrough infections. Of these, 9 were male and 14 were female. Four were asymptomatic and 19 were symptomatic. Of the 19 symptomatic, 18 had mild and 1 had severe disease. Mild infections presented with upper respiratory tract symptoms. Duration of symptoms ranged from 4 to 27 days with an average of 10 days. Timing of breakthrough infections ranged from 35 to 212 days after the second dose of COVID-19 vaccine with a mean of 86 days. Contact with confirmed cases was reported in 14 of 23 cases, 13 were from household members and none within the SLICE and CLARO programs. Conclusion Our study showed that even in the midst of the Delta surge, low breakthrough infection rate with mostly mildly symptomatic cases and no case transmissions within the SLICE and CLARO programs are possible with vaccination, regular health surveillance, and strict adherence to minimum health protocols.